PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. ASURANSI JIWASRAYA (PERSERO) KANTOR WILAYAH PEKANBARU - Butar-butar, Moina Elfrida; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of performance appraisal and development of employees to work productivity of employees at PT Bank of North Sumatra branch Sidikalang partially and simultaneously. Dimensions are used in performance assessment consists of a standard-setting work, performance assessment and provision of feedback. Dimensions variable employee development consists of materials, instructors and facilities. And dimensions for the independent variables (productivity of employees) consists of ability, morale, efficiency, improvement of the work, the quality, research and development diri.Metode used is descriptive analysis method and multiple linear analysis method that produces output t test, test F, and test the determinant (Â²). Processing data using SPSS 20.0 program.The results showed that the provision of compensation and motivation simultaneously significant effect on employee performance. It can be seen from the F-count = 121 859> F-table = 3.18. So that the figures obtained R2 (R Square) of 0.824 or 82.4%. This shows that the percentage contribution of the influence of the independent variable (compensation and motivation) on the dependent variable (performance of employees) amounted to 82.4% and strong relationships with a large award is 0.824. While the remaining percentage of 17.6% (100% - 82.4%) influenced by other variables not included in this study variables.Keywords: Compensation, Motivation, Employee Performance